2014
DOI: 10.1159/000361016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Biomarkers in Preeclampsia at Triage

Abstract: Introduction: To investigate the ability of cardiovascular plasma biomarkers to identify imminent preeclampsia (PE) among pregnant women at triage. Material and Methods: C-terminal pro-arginine vasopressin (copeptin), C-terminal pro-endothelin-1 (CT-proET-1), mid-regional pro-adrenomedullin (MR-proADM), and mid-regional pro-atrial natriuretic peptide (MR-proANP) were prospectively measured in pregnant women presenting at the obstetrical triage units of the University Hospitals of Basel and Zurich, Switzerland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…31 Three other studies have also observed increased maternal copeptin among PE cases. 29, 30, 32 Santillan et al prospectively observed a significant difference in copeptin levels beginning in the first trimester between 20 PE cases and 26 controls. 32 They also observed using an animal model that infusion of vasopressin during pregnancy in mice leads to the clinical phenotypes observed in PE.…”
Section: Discussionmentioning
confidence: 98%
“…31 Three other studies have also observed increased maternal copeptin among PE cases. 29, 30, 32 Santillan et al prospectively observed a significant difference in copeptin levels beginning in the first trimester between 20 PE cases and 26 controls. 32 They also observed using an animal model that infusion of vasopressin during pregnancy in mice leads to the clinical phenotypes observed in PE.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, during our revision process, Wellmann et al reported elevated MR-proADM in preeclampsia using a similarly sized cohort [15]. However, their study did not distinguish between mild and severe preeclampsia and included two key groups of patients that we excluded from our study: patients carrying multiple pregnancies and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…14 Earlier reports showed that copeptin is a potent predictor of preeclampsia and may be involved in its pathogenesis. 10 15 Furthermore, Santillan et al . 16 recently showed that elevated maternal plasma copeptin is a highly significant predictor of preeclampsia as early as the 6 th week of gestation.…”
Section: Introductionmentioning
confidence: 99%